2014
DOI: 10.1007/s00127-014-0851-y
|View full text |Cite
|
Sign up to set email alerts
|

A supportive family environment in childhood enhances the level and heritability of sense of coherence in early adulthood

Abstract: Purpose To analyze the effects of genetic and environmental factors on sense of coherence (SOC) in young adulthood and whether family environment measured in childhood modifies these effects. Methods SOC was measured at 20–27 years of age in 3,193 Finnish twins using the Antonovsky’s 13-item short scale. The twins and their parents had rated their emotional family environment independently when the twins were 12 years of age. The data were analyzed using applications of structural linear equation modeling to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 34 publications
2
20
0
1
Order By: Relevance
“…GRRs are another concept introduced by Antonovsky: they include factors like coping strategies, social support and knowledge which are deemed to reinforce and strengthen SoC in individuals. 11 Finally, recent research has suggested that a considerable amount of variation in individual SoC can be explained by genetic factors; 64 however, no suitable data for these cities are available to investigate this further.…”
Section: Discussionmentioning
confidence: 99%
“…GRRs are another concept introduced by Antonovsky: they include factors like coping strategies, social support and knowledge which are deemed to reinforce and strengthen SoC in individuals. 11 Finally, recent research has suggested that a considerable amount of variation in individual SoC can be explained by genetic factors; 64 however, no suitable data for these cities are available to investigate this further.…”
Section: Discussionmentioning
confidence: 99%
“…These include genetic association and functional analyses to identify the genes and genetic variation responsible for the familial aggregation highlighted by twin and family studies (van Dongen & Boomsma, 2012). Also much more sophisticated and multivariate approaches to twin data continue to yield new insights into the interplay of genetic and environmental influences on human health and behavior (Silventoinen, 2014).…”
Section: Age 30mentioning
confidence: 99%
“…More recently published research confirmed the results of the Swedish Twin Mother's Study. Silventoinen and colleagues analyzed the effects of genetic and environmental factors on the SOC in young adulthood among 3193 Finnish twins (Silventoinen et al, 2014). The twins and their parents rated their emotional family environment independently when the twins were 12 years of age.…”
Section: Genetic Factorsmentioning
confidence: 99%